Improvements in the rotorcraft fuel economy and environmental impact through multiple-landing mission strategy - Ali, Fakhre; Goulos, Ioannis; Pachidis, Vassilios (American Helicopter Society (AHS), 2016)
This paper presents an integrated rotorcraft multidisciplinary simulation framework, deployed for the comprehensive assessment of combined rotorcraft–powerplant systems performance at mission level. The proposed methodology comprises a wide-range of individual modelling theories applicable to rotorcraft performance and flight dynamics, gas turbine engine performance, and estimation of gaseous emissions (i.e. nitrogen oxides, NOx). The overall methodology has been deployed to conduct a comprehensive mission level feasibility study for a twin-engine light (TEL) rotorcraft, modeled after the Airbus Helicopters Bo105 configuration operating on a multiple-landing flying (MLF) mission approach compared to rotorcraft employing a conventional flying (CF) mission approach. The results of the analyses allow mission level assessment of the both aforementioned approaches for a wide-range of useful payload (UPL) values, mission range as well as mission level outputs (e.g. fuel burn, mission time, and gaseous emissions i.e. NOx). Furthermore, evaluation of engine cycle parameters (i.e. overall pressure ratio (OPR), turbine entry temperature (TET), and engine mass flow) are also carried out with respect to both approaches. The results acquired through the parametric analyses suggest that the MLF mission approach has the potential to significantly reduce rotorcraft mission fuel burn as well as gaseous emission (i.e. NOx). It has also been established through the acquired results that rotorcraft employing the MLF mission approach requires lower engine operating power throughout the entire mission duration, and therefore operates on a relatively lower engine OPR, combustor entry temperature, mass flow, rotational speed, and the TET compared to rotorcraft employing CF mission approach. It is emphasized that such operation of the engine can potentially improve the rate at which the engine components (i.e. compressor, combustor, and turbine) may deteriorate, thus the MLF mission approach can potentially provide further benefit in terms of engine maintenance and overall engine life. Finally it has been emphasised that the mission total range is a critical parameter in determining the level of benefit that can be attained from the employment of MLF mission approach.